Movie Discussion Club: A Teaching Model to Improve Integrated Skills in English - Winda Lutfiyanti (SAGA: Journal of English Language Teaching and Applied Linguistics, 2024)
This research aimed to design and develop a teaching model following the need analysis which showed that the learners needed a set of instructional system to improve their integrated skills in English. Eighteen freshmen of English Literature Department (S1) and English Department (D3) from academic year 2019/2020 were participated as subjects in developing the teaching model. In conducting this research, there are seven steps in the procedure of research and development including: 1) need analysis and reference study, 2) developing product, 3) preliminary field testing, 4) first revision, 5) expert validation, 6) second revision, and 7) final product (first version). The instruments used to collect data are interview, observation, and questionnaire. The model was designed referring to six fundamental elements of teaching model namely focus, syntax, principle of reaction, social system, support system, and application context then implemented in Movie Discussion Club. The data of the field testing showed that the learners’ integrated skills improved. Later on, the researcher used the note from this stage to revise the product. Moreover, expert validators checked the product and gave suggestions to make last adjustment. The final product of the research is a revised design of teaching model applied in Movie Discussion Club.